2007
DOI: 10.1007/s00432-007-0212-2
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione peroxidase, glutathione reductase and protein oxidation in patients with glioblastoma multiforme and transitional meningioma

Abstract: GPx and GRx decreased and POx increased significantly in both GBM and TM when compared to normal brain tissues. Further, clinical studies with a larger patient population are required to show the role(s) of antioxidant enzymes in brain tumors more accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Expression levels and activities of GR and GPx were decreased in patients with glioblastoma multiforme (GBM) and transitional meningioma (TM), when compared with normal brain tissues. However, protein oxidation levels measured by protein carbonyl content were increased in GBM and TM, perhaps because of the decreases in other antioxidant systems (185). The role of GR in zincinduced toxicity was shown by studies in human lung cell lines and rat astrocytes (6,193).…”
Section: Distribution Of Redox Systems In Nucleimentioning
confidence: 96%
“…Expression levels and activities of GR and GPx were decreased in patients with glioblastoma multiforme (GBM) and transitional meningioma (TM), when compared with normal brain tissues. However, protein oxidation levels measured by protein carbonyl content were increased in GBM and TM, perhaps because of the decreases in other antioxidant systems (185). The role of GR in zincinduced toxicity was shown by studies in human lung cell lines and rat astrocytes (6,193).…”
Section: Distribution Of Redox Systems In Nucleimentioning
confidence: 96%
“…Glioblastomas, like normal brain tissue, have low antioxidant activity. This is supported by several studies that have revealed depleted levels of ROS detoxification enzymes (gluthathione peroxidase and superoxide dismutase) in clinical glioblastomas examined from tumor patient explants (2729). Additionally, glioblastomas have been shown to increase the expression levels of the ROS generator, xanthine oxidase.…”
Section: Discussionmentioning
confidence: 57%
“…The creation of glioma tumor is a complex process involved neoplastic changes of cells, resistance to apoptosis, lack of cell cycle control and angiogenesis (12). Many studies showed that OS has a substantial role in these processes and modulation of OS can have a therapeutic potential in treatment (13)(14). It is demonstrated that pro-inflammatory cytokine and OS could interact and provoke each other and contribute to the development and progression of some diseases such as diabetes and cancer.…”
Section: Discussionmentioning
confidence: 99%